Analisis Peran Guru dalam Mengatasi Perundungan di Sekolah Dasar - Elawati, Elawati; Suandy, Imaculata Viviana; Beltapan, Noval Depati Allam; Giwangsa, Sendi Fauzi (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
This research is motivated by the widespread bullying that occurs in elementary schools. This does not only happen to students but also to teaching staff. Based on surveys and observation results, bullying occurs more often among students. This research was conducted to analyze the role of teachers in preventing and overcoming bullying that occurs in elementary schools from various factors that trigger bullying. The method used in this research is a qualitative method with a case study approach. Participants in this research were teachers from one of the elementary schools in Tanjungpandan, Belitung. This research concludes that the role of teachers in preventing and overcoming bullying in elementary schools is very important. Creating a safe and comfortable school environment, providing outreach regarding bullying at school, working together with parents so that they can provide the best for students while at school and at home. Recommendations for previous researchers can expand research locations where bullying is still widespread in schools so that they can provide improvements for preventing bullying in elementary schools.